Penerapan Pelatihan Higiene Sanitasi Untuk Meningkatkan Pengetahuan Bagi Penjamah Makanan Nasi Boran di Kota Lamongan - Nahdliyah Hita Pratiwi; Niken Purwidiani; Sri Handajani; Asrul Bahar (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to determine whether hygiene and sanitation training can improve knowledge for food handlers of boran rice in Lamongan City. This research method uses quantitative with an evaluative descriptive approach. Data collection techniques through Pre Test and Post Test questions. Research respondents were all food handlers of Boran rice in Lamongan city. a total of 20 people. with descriptive analysis techniques with the help of the SPSS (Statistical Package For Social Science) program. The results showed: by comparing the results of the pre-test and post-test, it can be seen that the training was quite effective in increasing participants' understanding and knowledge of hygiene and sanitation, because the average posttest answer of food handler respondents obtained a higher posttest score than when the pretest was conducted. Evidenced by the average Pre Test score was 66.75 and the average Post Test score was 73.25. Where the score is in the very good category. So it can be said that there is an effect of the application of sanitation hygiene training on increasing knowledge for food handlers of boran rice in Lamongan City.